2022
DOI: 10.1021/acsapm.2c00463
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chain Lengths on the Antibiofilm and Hemolytic Activities of Main-Chain Alternating Polysulfoniums

Abstract: Unlike antibiotics with accurate chemical structures, polydisperse chain lengths of synthetic polycations usually result in undesirable variations of antibacterial performance, which obstructs their wide applications in many areas. Herein, we propose that main-chain sulfonium-based polymers with alternating sequences may be used as a potential solution to tackle this issue. Through the thiol–epoxy “click” step-growth polymerization and methylation, alternating polysulfoniums can be facilely prepared with polyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…It is reported that a molecular weight ranging from 6000 to 50 000 g mol −1 has no obvious trend of antibacterial activity and biocompatibility linked to the changing of polymer chain length. [ 52 ] In this exploration, 15 PIm + s with Mn¯$\overline {{M_n}} $ ranging from 0.6 to 2.1 kDa were prepared. The detailed chemical structure information of them is displayed in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that a molecular weight ranging from 6000 to 50 000 g mol −1 has no obvious trend of antibacterial activity and biocompatibility linked to the changing of polymer chain length. [ 52 ] In this exploration, 15 PIm + s with Mn¯$\overline {{M_n}} $ ranging from 0.6 to 2.1 kDa were prepared. The detailed chemical structure information of them is displayed in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The culture of bacteria strains and the planktonic MIC and MBC assays were carried out according to the procedure described in our previous report. 17 For the antibacterial kinetic study, the suspensions of bacteria (2 × 10 6 CFU/ mL) in TSB were prepared, followed by the addition of the PolyS + polymer (MIC of PolyS + ), Rif (MIC of Rif), and PolyS + /Rif combination (MIC of PolyS + and MIC of Rif) solution. At different incubation times, the mixture was sampled, diluted 100 times, and then transferred onto TSB agar plates and spread evenly.…”
Section: Characterizationsmentioning
confidence: 99%
“…However, the majority of work in this area so far is usually based on the alkylation reaction with a complete conversion to maintain the alternating sequence definition from the precursor polymers. 12,17,19 Quantitatively manipulating the alkylation level of main-chain sulfonium-containing polymers as a means to balance the charge density/amphiphilicity and thus regulate their biological activity has not been demonstrated. Due to the unique membrane interruption ability, cationic polymers can be used as not only direct antibacterial agents but also antibiotic adjuvants to increase the potency of antibiotics in treating Gram-negative bacterial infections.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations